2018
DOI: 10.1155/2018/4183670
|View full text |Cite
|
Sign up to set email alerts
|

Gypenosides Attenuate Lipopolysaccharide‐Induced Neuroinflammation and Memory Impairment in Rats

Abstract: Neuroinflammation is deliberated a major factor in various neurodegenerative diseases. Gypenosides (GPS) have pharmacological properties with multiple beneficial effects including anti-inflammatory, antioxidative, and protective properties. In the present study, whether GPS could improve cognitive dysfunction and chronic inflammation caused by injecting lipopolysaccharide (LPS) in the hippocampus was investigated. Effects of GPS on inflammatory factors in the hippocampus and the downstream mechanisms of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Moreover, according to recent studies, LPS given intraperitoneally can activate astrocytes and microglial cells, inducing the processes of astrogliosis and microgliosis, respectively. Activation of both astrocytes and microglia induces neurotoxicity, neuroinflammation, and the production of ROS by stimulating proinflammatory mediators [7, 1216]. Badshah et al demonstrated the systemic administration of LPS to adult mice at a dose of 250 μ g/kg for 1 week-induced neuronal cell death by increasing the expression of caspase-3 and poly [ADP-ribose] polymerase 1 (PARP-1), triggering the mitochondrial apoptotic pathway [1].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to recent studies, LPS given intraperitoneally can activate astrocytes and microglial cells, inducing the processes of astrogliosis and microgliosis, respectively. Activation of both astrocytes and microglia induces neurotoxicity, neuroinflammation, and the production of ROS by stimulating proinflammatory mediators [7, 1216]. Badshah et al demonstrated the systemic administration of LPS to adult mice at a dose of 250 μ g/kg for 1 week-induced neuronal cell death by increasing the expression of caspase-3 and poly [ADP-ribose] polymerase 1 (PARP-1), triggering the mitochondrial apoptotic pathway [1].…”
Section: Introductionmentioning
confidence: 99%
“…Bariatric surgery promotes remission of diabetes mellitus and improves insulin resistance compared with medical intervention, but the mechanism is not very clear. It has been proposed that some potential mechanisms may be involved in the carbohydrate metabolism, including intestinal microflora metabolism [14], bile acid physiology [15] and a reduction in LPS level after surgery [5,6]. LPS, a component of the outer membrane of gramnegative bacteria, is formed by a phosphoglycolipid or lipid A that is covalently linked to a hydrophilic heteropolysaccharide [16].…”
Section: Discussionmentioning
confidence: 99%
“…LPS acts on target tissues such as adipose, skeletal muscle, and liver. These tissues have specific receptors which interact with LPS and induce the secretion of inflammatory cytokines and negatively regulate insulin signaling [5,6]. Two LPS-pathway proteins, including cluster of differentiation 14 (CD14) and LPSbinding protein (LBP), are widely used as indirect measures of response to the LPS endotoxin in numerous experimental studies [7].…”
mentioning
confidence: 99%
“…injection of 250 µg/kg/day LPS starting day 6, and CO control group received i.p. injection of 100 mg/kg/day Co for 12 consecutive days (Lee, Shim, & Lee, ).…”
Section: Methodsmentioning
confidence: 99%